Beta-Blocker in Heart Rate Control and Cardio Protection: The Role of ADRB1 Variants and HCN4 Regulation – A Systematic Review - Rasmaya Niruri; Zullies Ikawati; Agung Endro Nugroho; Habibie Arifianto (Indonesian Journal of Pharmacy, 2024)
Elevated heart rate is linked to adverse cardiovascular outcomes. Sinoatrial (SA) nodes, hyperpolarization-activated cyclic nucleotide-gated-4 (HCN4) channels, and beta1-adrenergic receptor (ADRB1) are responsible for generating the heart rate.  Beta-blockers have a cardioprotective effect on heart failure, including controlling heart rate. However, the responses to beta-blockers can vary among individuals. ADRB1 genetic variability may be contributed to the differential beta-blocker effect in heart failure.  HCN4 also performs a crucial function in the pacemaker cells of the heart. Exploring the effect of beta-blockers in pacemaker cells is expanding the view of their role and their therapeutic response in heart failure. The objectives of this study were to identify ADRB1 genetic variants affecting heart rate response in heart failure subjects with beta-blocker treatment and to explore the effect of beta-blockers on HCN4 channels and SA nodes. A systematic review was performed using three databases. Eight of 668 manuscripts were selected. The systematic review found that ADRB1 genetic variants (A145G (Ser49Gly) and C1165G (Arg389Gly)) can affect heart rate response in beta-blocker-treated heart failure. The study also found that the percentage of patients with the Ser49Ser-Gly389X haplotype achieved a heart rate target was higher than other haplotypes. Individuals with the Arg389Arg genotype necessitated a markedly increased amount of beta-blocker dose to reach the identical heart rate target compared to those with the Gly389X gene variation. In addition, the review found that carvedilol, a beta-blocker derivative, demonstrated beneficial effects in inhibiting HCN-gated channels.  Bisoprolol and carvedilol improved channel regulation in the SA Node by reversing the downregulation of HCN4 and sodium channels.  In general, this systematic review provides important insights into beta-blockers in treating heart failure, specifically concerning the genetic variability of ADRB1 and the beta-blockers effect on the SA node and HCN4 channels.